Which Seat Facilitates the Detection of Off-Seat Behaviours? An Inattentional Blindness Test on Location Effect in the Classroom - Cao, Shuqin; Wei, Xiuying; Hu, Jiangbo; Zhang, Hui (Frontiers in Psychology, 2022)
Off-seat behaviour refers to students leaving their seats and walking out of a classroom without the teacher noticing. This behaviour occurs in special education for students with certain special needs, which would lead to serious safety problems. This study carried out an inattentional blindness test to explore whether the location of seats in classrooms would impact teachers’ detection rate regarding off-seat behaviours. The participants were 126 pre-service teachers (Mage = 18.72 ± 0.723; 92% female) who were invited to perform the primary task of counting students raising their hands up whilst the disappearance of one of the students was introduced as an unexpected occurrence. The results show that peripheral seats were more detectable than the central ones for the teachers to notice the “missing student.” Meanwhile, the left and below oriented seats were more likely to be ignored compared to those that were right and upper oriented. These results suggest the existence of a location effect in the classroom that is associated with teachers’ attention regarding off-seat behaviour. This study has implications for classroom management in terms of arranging students’ seats appropriately to assist in increasing teachers’ identification of this hazard.